Discovery Sulfoglycomics and Identification of the Characteristic Fragment Ions for High-Sensitivity Precise Mapping of Adult Zebrafish Brain–Specific Glycotopes - Tseng, Huan-Chuan; Hsiao, Cheng-Te; Yamakawa, Nao; Guérardel, Yann; Khoo, Kay-Hooi (Frontiers in Molecular Biosciences, 2021)
Mass spectrometry-based high sensitivity mapping of terminal glycotopes relies on diagnostic MS2 and/or MS3 ions that can differentiate linkage and define location of substituents including sulfates. Unambiguous identification of the adult zebrafish glycotopes are particularly challenging due to additional presence of extra beta4-galactosylation on the basic building block of Galbeta1-4GlcNAc that can be fucosylated and variably sialylated by N-acetyl-, N-glycolyl or deaminated neuraminic acids. Building on previous ground work that have identified the various organ-specific N- and O-glycans of adult zebrafish, we show here all the major glycotopes of interest can be readily mapped by a direct nanoLC-MS/MS analysis of permethylated glycans. Homing in on the brain, intestine and ovary derived samples, organ-specific glycomic reference maps based on overlaid extracted ion chromatograms of resolved glycan species and composite charts of summed intensities of diagnostic MS2 ions representing the distribution and relative abundance of each of the glycotopes and sialic acid variants were established. Moreover, switching to negative mode analysis of sample fractions enriched in negatively charged glycans, we show, for the first time, that a full range of sulfated glycotopes is expressed in adult zebrafish. In particular, 3-O-sulfation of terminal Gal was commonly found, whereas terminal sulfated HexNAc as in GalNAcbeta1-4GlcNAc (LacdiNAc), and 3-O-sulfated hexuronic acid as in HNK-1 epitope (SO3-3GlcAbeta1-3Galbeta1-4GlcNAc), were identified only in brain, and not in the intestine or ovaries analyzed in parallel. Other characteristic structural features of sulfated O- and N-glycans along with their diagnostic ions detected in this discovery mode sulfoglycomic work collectively expands our adult zebrafish glycome-atlas, which can now allow a more complete navigation and probing of the underlying sulfotransferases and glycosyltransferases, in search of the functional relevance of zebrafish-specific glycotopes. Of particular importance is the knowledge of glycomic features distinct from those of human when using adult zebrafish as an alternative vertebrate model other than mouse for brain-related glyco-neurobiology studies.